Evaluation of the Genetic Variation Spectrum Related to Corneal Dystrophy in a Large Cohort - Li, Wei; Qu, Ning; Li, Jian-Kang; Li, Yu-Xin; Han, Dong-Ming; Chen, Yi-Xi; Tian, Le; Shao, Kang; Yang, Wen; Wang, Zhuo-Shi; Chen, Xuan; Jin, Xiao-Ying; et al. (Frontiers in Cell and Developmental Biology, 2021)
Aims To characterize the genetic landscape and mutation spectrum of patients with corneal dystrophies (CDs) in a large Han ethnic Chinese Cohort with inherited eye diseases (IEDs). Methods Retrospective study. A large IED cohort was recruited in this study, including 69 clinically diagnosed CD patients, as well as other types of eye diseases patients and healthy family members as controls. The 792 genes on the Target_Eye_792_V2 chip were used to screen all common IEDs in our studies, including 22 CD-related genes. Results We identified 2334 distinct high-quality variants on 22 CD-related genes in a large IEDs cohort. A total of 21 distinct pathogenic or likely pathogenic mutations were identified, and the remaining 2313 variants in our IED cohort had no evidence of CD-related pathogenicity. Overall, 81.16% (n = 56/69) of CD patients received definite molecular diagnoses, and transforming growth factor-beta-induced protein (TGFBI), CHTS6, and SLC4A11 genes covered 91.07, 7.14, and 1.79% of the diagnosed cases, respectively. Twelve distinct disease-associated mutations in the TGFBI gene were identified, 11 of which were previously reported and one is novel. Four of these TGFBI mutations (p.D123H, p.M502V, p.P501T, and p.P501A) were redefined as likely benign in our Han ethnic Chinese IED cohort after performing clinical variant interpretation. These four TGFBI mutations were detected in asymptomatic individuals but not in CD patients, especially the previously reported disease-causing mutation p.P501T. Among 56 CD patients with positive detected mutations, the recurrent TGFBI mutations were p.R124H, p.R555W, p.R124C, p.R555Q, and p.R124L, and the proportions were 32.14, 19.64, 14.29, 10.71, and 3.57%, respectively. Twelve distinct pathogenic or likely pathogenic mutations of CHTS6 were detected in 28 individuals. The recurrent mutations were p.Y358H, p.R140X, and p.R205W, and the proportions were 25.00, 21.43, and 14.29%, respectively. All individuals associated with TGFBI were missense mutations; 74.19% associated with CHTS6 mutations were missense mutations, and 25.81% were non-sense mutations. Hot regions were located in exons 4 and 12 of TGFBI individuals and located in exon 3 of CHTS6 individuals. No de novo mutations were identified. Conclusion For the first time, our large cohort study systematically described the variation spectrum of 22 CD-related genes and evaluated the frequency and pathogenicity of all 2334 distinct high-quality variants in our IED cohort. Our research will provide East Asia and other populations with baseline data from a Han ethnic population-specific level.